A Social Pragmatic Study of Selected Women Sex-Related Yorùbá Proverbs Translated In English - Onipede, Festus Moses; Olofin, Victoria Oluwakemi (Universitas Andalas, 2025)
Language performs important social functions. Language serves as a means of passing along a people’s culture from one generation to the next. The Yoruba people are well renowned for having a strong oral tradition and cultural inheritance, particularly with regard to the use of proverbs. Studies have also looked into how Yoruba proverbs contribute to the contradictions in gender roles in the region. Research has also examined the ways in which gender roles in the area are contradicted by Yoruba proverbs. The majority of research on Yoruba proverbs has been on their semantic structures, categories, and uses in interpersonal and conflict resolution communication. The goal of this research is to better understand the situations in which women’s gender is inaccurately portrayed by looking at the ideologies that underlie the poor representations of women in proverbs and the most prevalent illocutionary actions used to spread these unfavourable impressions. The Yorùbâ proverbs (Olawole, 1998, Olojede, 2012, Olasupo et al. 2012, Owomoyela, 2005, Ademowo and Balogun, 2015, interview) were culled down to a selection of nineteen proverbs. Because proverbs are contextualised in Yoruba culture, the study incorporates context, which is a component of Lawal’s pragmatic theory from 2012. The six philosophical background levels and the Yoruba worldview are taken into consideration when analysing the work. These include the levels of context, language, psychology, cosmology, sociology, and society. The findings demonstrated that instances of illocutionary behaviour included confirming, warning, claiming, saying, forecasting, admonishing, and judging. When males feel they have harmed their female counterparts, they use proverbs to accentuate their views. This is the overall context in which these sayings are used. These sayings are meant to dissuade women from having original thought processes. Declarative illocutionary acts are a common indicator of male dominance over female counterparts. As a result, proverbs that originate from Yoruba cultural concepts reinforce the derogatory portrayal of women.